1992
DOI: 10.1177/107769909206900320
|View full text |Cite
|
Sign up to set email alerts
|

Channel One and Commercials in Classrooms: Advertising Content Aimed at Students

Abstract: A content analysis of a sample of advertisements on Whittle Communication's commercially sponsored daily 12-minute television program for high school students shows that 86% of the commercials were for products and 14% were public service announcements. Values stressed in commercials were those emphasizing leisure/pleasure, appeamnce/sexuality, wisdom and independence. Dominant themes were being popular, having friends, having f u n and being attractive. The commercials were the same as those on regular televi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
17
0

Year Published

2003
2003
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(17 citation statements)
references
References 0 publications
0
17
0
Order By: Relevance
“…Advertisements also display a level of wealth that is unattainable for the average consumer and show idealized versions of life within the context of the advertisement. 13,17,[20][21][22] Such tactics create associations between the product and desirable outcomes and also teach consumptive behavior through modeling. 35,36 Contrary to expectations, we did not find support for our hypothesis that materialism leads to decreased life satisfaction among children, which has convincingly been demonstrated among adults.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Advertisements also display a level of wealth that is unattainable for the average consumer and show idealized versions of life within the context of the advertisement. 13,17,[20][21][22] Such tactics create associations between the product and desirable outcomes and also teach consumptive behavior through modeling. 35,36 Contrary to expectations, we did not find support for our hypothesis that materialism leads to decreased life satisfaction among children, which has convincingly been demonstrated among adults.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, advertising promotes the idea that possessions are a way to increase happiness and to compensate for low life satisfaction. 13,17,[20][21][22] In relation to H2, unhappy children might be more likely to become more materialistic if they are frequently exposed to advertising, implying that advertising reinforces the negative effect of life satisfaction on materialism (hypothesis 4, H4).…”
mentioning
confidence: 92%
See 1 more Smart Citation
“…On a typical day, student viewers will see ads for candies, snacks, and soft drinks. Wulfemeyer and Mueller (1992) analyzed the content of 99 commercials appearing in five randomly selected Channel One programs over a 5-week period. They reported that 86% of the ads were for products and that the products dealt almost exclusively with clothing, food, and physical attractiveness concerns (U.S. General Accounting Office, 2000, pp.…”
mentioning
confidence: 99%
“…Developing materialistic and consumerist values for the youngest ones increases the rate of dissatisfaction due to unfulfilled expectations, encourages conflicts between parents and children and produces other risky behaviors among children (Matović, 2012).The values that are often forwarded through the advertisements are promoting unrealistic and unattainable life, and for the youngest targeted population bring about disappointment and anxiety. Unequivocally, larger exposure to advertisements leads to the adoption of materialistic values (Kasser, Ryan, Couchman and Sheldon, 2004;Pollay, 1986, andWulfemeyer &Mueller, 1992) Media literate children and young people should recognize and understand the impact of the media, as well as comprehend the ethical dimensions of the functioning of the media (Tjurou, 2012), whereby the dialogic teaching and learning constitute an important component in education, and self-criticism would be a constant focus of educational work (Milutinović, 2013). Finally, H a3: Advertising increases materialistic values in children.…”
Section: Introductionmentioning
confidence: 99%